Urban Morphology and Energy Performance: Spatial-Simulation Assessment from Hebron, Palestine - Aburmalah, Azeez Ezaldeen Ahmad; Üzümcüoğlu, Doğa (Alanya Üniversitesi, 2025)
Urban morphology critically governs residential energy demand, yet empirical evidence from semi-arid, geopolitically constrained cities remains scarce. This study quantifies the influence of neighbourhood form on heating and cooling loads in Hebron, Palestine. Three morphologically distinct districts—Old City (compact), Zeitoun (semi-structured) and Al Sheikh (unplanned sprawl)—were mapped in ArcGIS Pro to derive Floor Space Index, Ground Space Index and Open Space Ratio. Prototype mid-rise dwellings were modelled in DesignBuilder and simulated with EnergyPlus under identical boundary conditions. Pearson correlations and ANOVA assessed relationships between morphological variables and annual loads. Results show cooling demand decreases by 34 % as FSI rises from 0.7 to 1.2, whereas heating demand doubles under the same densification. The moderately dense Zeitoun configuration (FSI≈1.0, OSR≈1.6) achieved the lowest combined energy use, outperforming both extreme forms. Findings demonstrate that mid-rise, medium-density layouts balance summer shading with winter solar access, offering a viable pathway for energy-aware expansion in semi-arid contexts. The integrated spatial-simulation framework provides planners with transferable metrics for zoning and retrofit prioritisation, supporting climate-responsive urban policy across the Middle East. Future research should incorporate behavioural patterns and multiple building typologies to refine these benchmarks under climate-change scenarios.